Atypical case of Wilson's disease with psychotic onset, low 24 hour urine copper and the absence of Kayser-Fleischer rings - Krstić Dragan; Antonijević Jadranka; Špirić Željko (Vojnosanitetski Pregled)
Introduction. Wilson's disease is typically manifested in two clinical forms, neurological and hepatic and in rare cases it starts with psychiatric symptoms exclusively. We presented a rare atypical case of Wilson's disease with psychotic onset. Case report. A 22-year-old male patient was initially presented with predominant signs and symptoms of psychiatric disorder and then later with the development of neurological signs and symptoms. Neuroimaging, detected metal deposits in central nervous system (CNS) but not in peripheral organs, while serum analysis excluded pantothenate-kinase associated neurodegeneration (PKAN) and aceruloplasminemia. In favor of the diagnosis of Wilson's disease there were reduced concentrations of copper and ceruloplasmin concentrations and metal deposits in CNS, but other pathognomonic signs and symptoms were absent: in-creased copper in urine, Kayser-Fleischer rings in Descemet’s corneal membrane and deposits of copper in liver. Introduction of penicillamine treatment resulted in improvement in mental and general health of the patient. Molecular genetic analysis definitely confirmed the diagnosis of Wilson's disease. Conclusion. Wilson's disease can remain undetected for a long period of time if masked with dominant or exclusive psychiatric symptoms. If clear clinical symptoms and signs, and unambiguous laboratory findings are not present, it is necessary to perform molecular genetic analysis to confirm the definitive diagnosis.